The Impact of COVID-19-Related Shutdown Measures on the Training Habits and Perceptions of Athletes in the United States: A Brief Research Report - Jagim, Andrew R.; Luedke, Joel; Fitzpatrick, Austin; Winkelman, Greg; Erickson, Jacob L.; Askow, Andrew T.; Camic, Clayton L. (Frontiers in Sports and Active Living, 2020)
The purpose of the current study was to examine the impact of COVID-19 government-enforced shutdown measures on the training habits and perceptions of athletes. A web-based electronic survey was developed and distributed online to athletes. The survey contained questions regarding currently available resources, changes in weekly training habits, and perceptions of training such as intensity, motivation, and enjoyment. A total of 105 (males: n = 31; females: n = 74) athletes completed the survey (mean ± SD age = 19.86 ± 2.13 years). Ninety-nine (94.3%) athletes continued to receive guidance from their primary sport coach or strength training staff. There was a significant (p < 0.001) decrease (mean ± SD) in self-reported participation time for strength training (−1.65 ± 4.32 h. week−1), endurance (−1.47 ± 3.93 h. week−1), and mobility (−1.09 ± 2.24 h. week−1), with the largest reduction coming from participation time in sport-specific activities (−6.44 ± 6.28 h. week−1) pre- to post-shutdown. When asked to rate their current state of emotional well-being using a visual analog scale of 0–100, with 100 being exceptional, the mean score was 51.6 ± 19.6 AU. Athletes experienced notable reductions in training frequency and time spent completing various training related activities. In the future, practitioners should have preparations in place in the event of another lockdown period or future pandemic to avoid or minimize significant disruptions in training. Special considerations may be needed when athletes are allowed to return to sport in the event of significant levels of detraining that may have occurred.